2021
DOI: 10.3390/ijms22094778
|View full text |Cite
|
Sign up to set email alerts
|

Insights on the Functional Role of Beta-Glucans in Fungal Immunity Using Receptor-Deficient Mouse Models

Abstract: Understanding the host anti-fungal immunity induced by beta-glucan has been one of the most challenging conundrums in the field of biomedical research. During the last couple of decades, insights on the role of beta-glucan in fungal disease progression, susceptibility, and resistance have been greatly augmented through the utility of various beta-glucan cognate receptor-deficient mouse models. Analysis of dectin-1 knockout mice has clarified the downstream signaling pathways and adaptive effector responses tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 137 publications
(180 reference statements)
0
5
0
Order By: Relevance
“…The antibacterial properties of beta-glucans are also known and well described [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ], but little is known about their direct action on fungi and possible direct antifungal activity. So far, research has focused on understanding the interactions between host cells (mainly animal) and beta-glucan and the host anti-fungal immunity induced by this compound [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The antibacterial properties of beta-glucans are also known and well described [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ], but little is known about their direct action on fungi and possible direct antifungal activity. So far, research has focused on understanding the interactions between host cells (mainly animal) and beta-glucan and the host anti-fungal immunity induced by this compound [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent development of various molecular biological techniques has enabled to elucidate detailed mechanisms for many diseases, however, establishing animal models is still a critical way to better reflect disease progression, such as infectious diseases that always require to evaluate host-pathogen’s interactions [ 1 , 2 ]. Streptococcus pneumoniae is a Gram-positive bacterium which is a particular challenge for neonates and the elderly adults.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, we previously showed that the CLR Dectin-1, which recognizes b-glucans on fungal cell walls and plays an important role in protection from fungal infection by inducing cytokines and T helper 17 (Th17) cell differentiation through activation of an immunoreceptor tyrosine-based activation motif (ITAM) in the cytoplasmic domain (Saijo et al, 2007;Tang et al, 2015;Desamero et al, 2021), induces antimicrobial protein S100A8 in the intestine by binding b-glucans in foods (Tang et al, 2015). Because the S100A8/A9 complex inhibits the growth of bacteria such as Lactobacillus murinus that can induce regulatory T (Treg) cell differentiation, Treg cell levels are low in mice fed food containing normal levels of b-glucans (Tang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%